Piano Sonata no. 1 in F minor, op. 2, no. 1, published by André - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Germany; Johann André; Offenbach am Main and Leipzig, 2024)
Piano Sonata no. 1 in F minor, op. 2, no. 1, published by J. André in the Sonates pour Pianoforte, from André's Oeuvres de L. van Beethoven pour le pianoforté seul & à quatre mains, originally published between 1804-1838. With additional imprint on Ewer & Co. at 72, Newgate St.